Theaflavin-Containing Black Tea Extract: A Potential DNA Methyltransferase Inhibitor in Human Colon Cancer Cells and Ehrlich Ascites Carcinoma-Induced Solid Tumors in Mice. - Bhattacharya, Ritwija; Chatterjee, Ranodeep; Mandal, Abul Kalam Azad; Mukhopadhyay, Aniruddha; Basu, Soumalee; Giri, Ashok Kumar; Chatterji, Urmi; Bhattacharjee, Pritha (Nutrition & Cancer, 2021)
Tea is the most popularly consumed beverage in the world. Theaflavin and thearubigins are the key bioactive compounds of black tea that have anticarcinogenic properties as reported in several studies. However, the epigenetic potential of these compounds has not yet been explored. DNA methyltransferase (DNMT) enzymes induce methylation of DNA at cytosine residues and play a significant role in epigenetic regulation and cancer therapy. The present study has explored the role of black tea as a DNMT inhibitor in the prevention of cancer. Herein, the effect of theaflavin has been studied in colon cancer cell line (HCT-116) and EAC-induced solid tumors in mice. It was found that theaflavin prevented cell proliferation and inhibited tumor progression as well. In silico study showed that theaflavin interacted with DNMT1 and DNMT3a enzymes and blocked their activity. Theaflavin also decreased DNMT activity In Vitro and In Vivo as evident from the DNMT activity assay. Results of immunohistochemistry revealed that theaflavin reduced DNMT expression in the tumors of mice. Taken together, our findings showed that theaflavin has a potential role as a DNMT inhibitor in HCT-116 cell line and EAC induced solid tumors in mice.